Comment on “Correlation Quantum Dynamics between an Electron and D+2 Molecule with Attosecond Resolution” - Tong, X. M.; Zhao, Z. X.; Lin, C. D. (My University, 2006)
A Comment on the Letter by Jie Hu, Ke-Li Han, and Guo-Zhong He, Phys. Rev. Lett. 95, 123001 (2005). The authors of the Letter offer a Reply.